I was having some difficulties when trying to use Armstrong axiom to solve functional dependencies.

R (A,B,C,D,E,F)
Given FD = { A->CD , C->BE, B->F, F->A }
Prove A-> BF

By using closure, for A, I get {A,C,D,B,E,F} so I know A->BF is valid.

So I came out with these to prove using Axiom:

CD->BED (Augmentation)
A->BED (Transitivity)
BED->FED (Augmentation)
A->FED (Transitivity)

Then from there, I am lost. Anybody knows how to prove it?

Thanks in advance.


1 Answer 1


Here is a possible derivation:

 1. A → CD   (given)
 2. C → BE   (given)
 3. CD → BED (by augmentation of 2 with D)
 4. A → BED  (by transitivity of 1 and 3)
 5. B → F    (given)
 6. B → BF   (by augmentation of 5 with B)
 7. BED → B  (by reflexivity)
 8. A → B    (by transitivity of 4 and 7)
 9. A → BF   (by transitivity of 8 and 6)

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.